JEE Advanced Binomial Theorem 2

Calculus Level 5

1 + ( 1 3 × 1 2 ) + ( 1 3 × 4 3 × 1 2 2 × 1 2 ! ) + ( 1 3 × 4 3 × 7 3 × 1 2 3 × 1 3 ! ) + n terms 1+\left ( \dfrac{1}{3}\times\dfrac{1}{2} \right ) + \left ( \dfrac{1}{3}\times\dfrac{4}{3}\times\dfrac{1}{2^2}\times\dfrac{1}{2!} \right )+\left ( \dfrac{1}{3}\times\dfrac{4}{3}\times\dfrac{7}{3}\times\dfrac{1}{2^3}\times\dfrac{1}{3!} \right ) +\cdots n \text{ terms}

For natural numbers n n , let S n S_n be the value of the above expression

Suppose that for positive integers a , b , c , d a,b,c,d with gcd ( a , b ) = gcd ( c , d ) = 1 \text{gcd}(a,b) = \text{gcd}(c,d) = 1 , we have

lim n S n = ( a b ) c d \displaystyle\lim_{n\rightarrow\infty} S_n=\left (\dfrac{a}{b}\right )^\dfrac{c}{d}

What is the value of a + b + c + d a+b+c+d ?

This is a part of My Picks for JEE Advanced 2


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kishlaya Jaiswal
Feb 25, 2015

We observe the expansion of ( 1 x ) ( n + 1 ) (1-x)^{-(n+1)} .using Negative Binomial Theorem (aka Newton's Generalized Binomial Theorem)

( 1 1 x ) n + 1 = k 0 ( n + k n ) x k = ( n n ) + ( n + 1 n ) x + ( n + 2 n ) x 2 + ( n + 3 n ) x 3 + = 1 + ( n + 1 ) x + ( n + 1 ) ( n + 2 ) 2 ! x 2 + ( n + 1 ) ( n + 2 ) ( n + 3 ) 3 ! x 3 + \begin{aligned} \left(\frac{1}{1-x}\right)^{n+1} & = & \sum_{k \geq 0} \binom{n+k}{n} x^k \\ & = & \binom{n}{n} + \binom{n+1}{n} x + \binom{n+2}{n} x^2 + \binom{n+3}{n} x^3 + \ldots \\ & = & 1 + (n+1)x + \frac{(n+1)(n+2)}{2!} x^2 + \frac{(n+1)(n+2)(n+3)}{3!} x^3 + \ldots \\ \end{aligned}

Plugging x = 1 2 x=\frac{1}{2} and n = 2 3 n=\frac{-2}{3} , yields our desired result as

2 1 / 3 = ( 1 1 1 2 ) 1 / 3 = 1 + 1 3 × 1 2 + 1 3 × 4 3 × 1 2 2 × 1 2 ! + 1 3 × 4 3 × 7 3 × 1 2 3 × 1 3 ! + 2^{1/3} = \left(\frac{1}{1-\frac{1}{2}}\right)^{1/3} = 1 + \frac{1}{3}\times \frac{1}{2} + \frac{1}{3}\times \frac{4}{3}\times \frac{1}{2^2}\times \frac{1}{2!} \\ \qquad + \frac{1}{3}\times \frac{4}{3}\times \frac{7}{3}\times \frac{1}{2^3}\times \frac{1}{3!} + \ldots

Thus, ( a b ) c d = ( 2 1 ) 1 3 \left(\frac{a}{b}\right)^{\frac{c}{d}} = \left(\frac{2}{1}\right)^{\frac{1}{3}}

And hence, a + b + c + d = 2 + 1 + 1 + 3 = 7 a+b+c+d = 2+1+1+3 = \boxed{7}

Same way! except yours is much better, i couldnt observe it so well so i found a recurrence between the coefficient of powers of 1 6 r 1 \frac{1}{6^{r-1}}

namely a i + 1 ( i + 2 ) = a i ( 3 i + 4 ) \\ { a }_{ i+1 }(i+2)={ a }_{ i }(3i+4)\\

(i greater than or 0, also a i a_i = T r 2 ) T_{r-2}) where t is term of series (and (r-2) is its subscript)

and then used generating function to get a differential which upon solving gave me

( 1 ( 3 x 1 ) 1 3 + 1 ) 1 x = T 2 + x T 3 + x 2 T 4 . . . . -(\frac { 1 }{ (3x-1)^{ \frac { 1 }{ 3 } } } +1)\frac { 1 }{ x } \quad =\quad { T }_{ 2 }+x{ T }_{ 3 }+{ x }^{ 2 }{ T }_{ 4 }....

now i put 1/6 = x , then again multiplied by 1/6 and added t 1 t_1 =1

to get 2 1 / 3 2^{1/3}

thus 7,

Awesome question @Pranjal , thanks cause i learnt the whole of generating functions to solve this problem and it was worth it,

Mvs Saketh - 6 years, 3 months ago

Log in to reply

Yep, generating functions is also a nice way to approach it.

Actually, I never thought of proceeding with it.

Nice Job. +1

Kishlaya Jaiswal - 6 years, 3 months ago

How to use generating function for obtaining what is described as namely.

Athul Nambolan - 6 years, 2 months ago

Why don't we directly use ( 1 + x ) n = 1 + n x + n ( n 1 ) 2 ! x 2 + . . . (1+x)^n = 1 + nx + \frac{n(n-1)}{2!}x^2 + ... with n = 1 / 3 n = -1/3 and x = 1 / 2 x = -1/2 instead of using ( 1 x ) ( n + 1 ) (1-x)^{-(n+1)} ?

Siddhartha Srivastava - 6 years, 3 months ago

Log in to reply

Just because the expansion of ( 1 x ) ( n + 1 ) (1-x)^{-(n+1)} looks more cleaner than the other one, to me.

( 1 x ) ( n + 1 ) = k = 0 ( n + k n ) x k (1-x)^{-(n+1)} = \sum_{k=0}^\infty {n+k \choose n} x^k

Anyway, you can also proceed using ( 1 + x ) n = 1 + n x + n ( n 1 ) 2 ! x 2 + (1+x)^{n} = 1+nx+\frac{n(n-1)}{2!}x^2 + \ldots . And actually, there is no difference between both of them because eventually you are taking n = 1 3 n = \frac{-1}{3} (which is negative) whereas the expansion which I have used is infact, the general expression for negative n n . So actually, you can say that they both are one and the same thing.

Kishlaya Jaiswal - 6 years, 3 months ago

Log in to reply

To each his own I guess. I was just asking because I thought the formula I wrote is more common. NCERT jindabad. xD

Siddhartha Srivastava - 6 years, 3 months ago

How can we prove that the limit Sn (n tends to infinity) turns out to be that binomial term (1-x)^p where x=1/2 & p =-1/3

Mayank Jha - 4 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...